Β-Glucan bioactivities from Cystobasidium benthicum in Totoaba macdonaldi thymus cells. Issue 119 (December 2021) - Reyes-Becerril, Martha; Angulo, Miriam; Sanchez, Veronica; Machuca, Cristian; Méndez-Martínez, Yuniel; Angulo, Carlos
Abstract: The overuse of antibiotics in aquaculture has led to serious concerns on microbial resistance and chemical residues. Novel sources of immunostimulants could help to solve this problem by stimulating the immune system to fight against pathogens. Therefore, this study aims to explore the immunostimulant potential of Cystobacidium benthicum -β-glucans ( Cb -βG) using thymus cells from Totoaba ( Totoaba macdonaldi ), a recently farmed fish species in Mexico. The Cb -βG was characterized and tested for its own antioxidant capacity. Then, a Cb -βG safety experiment was carried out in thymus cells by evaluating the effects on immune parameters and immune-related genes. Cb -βG had a molecular weight of 2.32 kDa, comprised of β-1, 3–1, 6-glucan (53.4%), and showed strong antioxidant capacity compared to that of the positive antioxidant control. Cb -βG had no toxic effects of thymus cells and enhanced phagocytic, respiratory burst, myeloperoxidase and superoxide activities. Additionally, immune-related genes implicated in recognition and effector functions of yeast glucans were up-regulated (Toll like receptor 2, C-type lectin family 17 member A, colony-stimulating factor 1 receptor 2, macrophage mannose receptor 1, and Interleukin-1β). In conclusion, the glucan -characterized physically-chemically from the yeast C. benthicum ( Cb -βG)- was safe, had strong antioxidant capacity to scavenge free radicals, and stimulated immune parameters and immune-related gene expressions on thymus cells from Totoaba macdonaldi . Highlights: Cystobacidium benthicum -β-glucans ( Cb -βG) was chemically characterized. Cb -βG had own antioxidant capacity. Cb -βG enhanced in immune parameters and immune-related genes in Totoaba macdonaldi thymus cells. Cb -βG could be considered a potential immunostimulant for farmed Totoaba in Mexico.